Identifikasi Perkembangan Kognitif Anak Kelas A di Gugus PAUD Kecamatan Selong Kabupaten Lombok Timur - Novita Meirianti; I Nyoman Suarta; Muazar Habibi; Nurhasanah Nurhasanah (Indonesian Journal of Elementary and Childhood Education, 2022)
Today's early childhood education institutions emphasize the cognitive development of children. Each school has its own way of developing children's cognitive development, this is the background for research on identifying children's cognitive development. The formulation of the research problem is how is the cognitive development of children in the aspects of learning and problem solving, how is the cognitive development of children in the aspect of logical thinking, and how is the cognitive development of children in the aspect of symbolic thinking. The research objective is to determine children's cognitive development in learning and problem solving aspects, logical thinking aspects, symbolic thinking aspects. The type of research used is qualitative which then the results of the research will be described. The research subjects were 30 children who were taken by random proportional random sampling technique. Data collection techniques in this study used the documentation method. Data processing techniques are triangulation, reduction, data presentation, and drawing conclusions. The results of the research on the first aspect of learning and problem solving on the indicator of knowing how to use play equipment as many as 6 children (19.98%) had not yet developed, there were six indicators with a high percentage of 17 children (56.61%) developing as expected. The second aspect of thinking logically on the indicator of knowing the causes and effects of something is that there is one child (3.33%) who has not yet developed. The indicators of knowing coarse-fine concepts, knowing geometric shapes have a percentage of 17 children (56.61%) developing as expected. The third aspect is symbolic thinking, the indicator of knowing full names and knowing the names of family members has a high percentage of 18 children (59.94%). Based on the results of the study, it can be concluded that the cognitive development of children in the Early Childhood Education Cluster, Selong District, East Lombok Regency is developing as expected.